2014
DOI: 10.2478/micrnat-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization-based detection of microRNAs in human diseases

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate various aspects of gene expression in physiology and development. Links between miRNAs and the initiation and progression of human diseases are becoming increasingly apparent. The development of methods to detect the subcellular and tissue localization of miRNAs is essential for understanding their biological role in homeostasis. In this review, we discuss how in situ hybridization can complement tissuelevel miRNA expression profiling and its role as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…Detection methods that incorporate the context of altered expression, such as multiplex ISH/immunohistochemistry assays, may provide additional validation tools for altered miRNA expression. 13 , 93 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection methods that incorporate the context of altered expression, such as multiplex ISH/immunohistochemistry assays, may provide additional validation tools for altered miRNA expression. 13 , 93 …”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization (ISH) assays are a powerful tool to determine altered miRNA expression at single-cell resolution and to assess the contribution of reactive stroma and immune response. 13 , 93 In breast phyllodes tumors, 94 as well as in colorectal 95 and pancreatic cancer, 96 upregulation of miR-21 expression promotes myofibrogenesis and regulates antimetastatic and proapoptotic target genes, including RECK (reversion-inducing cysteine-rich protein with kazal motifs), SPRY1/2 (Sprouty homolog 1/2 of Drosophila gene), PDCD-4 (programed cell death 4), and PTEN . We have recently shown that high levels of miR-21 expression in the stromal compartment in a cohort of 105 early-stage TNBC cases correlated with shorter recurrence-free and breast cancer–specific survival.…”
Section: Mirna Biomarkers and Therapeutic Opportunities In Tnbc Withomentioning
confidence: 99%
“…In the present study, we evaluated the expression of miR-361-5p by ISH analysis. Compared with other methods, ISH can visualize microRNA expression at the cellular level, so it is the only method that can directly assess the actual distribution of miRNAs (26,27). ISH analysis can thereby provide more precise information.…”
Section: Discussionmentioning
confidence: 99%
“…Formalin fixed paraffin embedded (FFPE) tissues were sectioned at 4 µm for ISH assay. DIG (digoxigenin) labeled anti-sense miR-21 oligonucleotide probe (5'-TCAACATCAG-TCTGATAAGCTA -3') was purchased from Boster (China) and used as the probe in the ISH assay as previously described [11]. Briefly, the FFPE sections were deparaffinized, rehydrated, and blocked for peroxidase activity, followed by proteinase K digestion and PBS (0.5M, pH 7.4) rinsing.…”
Section: In Situ Hybridization (Ish)mentioning
confidence: 99%